Intranasal Delivery of MVA Vector Vaccine Induces Effective Pulmonary Immunity Against SARS-CoV-2 in Rodents - Bošnjak, Berislav; Odak, Ivan; Barros-Martins, Joana; Sandrock, Inga; Hammerschmidt, Swantje I.; Permanyer, Marc; Patzer, Gwendolyn E.; Greorgiev, Hristo; Gutierrez Jauregui, Rodrigo; Tscherne, Alina; Schwarz, Jan Hendrik; Kalodimou, Georgia; et al. (Frontiers in Immunology, 2021)
Antigen-specific tissue resident memory T cells (Trms) and neutralizing IgA antibodies provide the most effective protection of the lungs from viral infections. To induce those essential components of lung immunity against SARS-CoV-2, we tested various immunization protocols involving intranasal delivery of a novel Modified Vaccinia virus Ankara (MVA)-SARS-2-spike vaccine candidate. We show that a single intranasal MVA-SARS-CoV-2-S application in mice strongly induced pulmonary spike-specific CD8+ T cells, albeit restricted production of neutralizing antibodies. In prime-boost protocols, intranasal booster vaccine delivery proved to be crucial for a massive expansion of systemic and lung tissue-resident spike-specific CD8+ T cells and development of TH1 - but not TH2 - CD4+ T cells. Likewise, very high titers of IgG and IgA anti-spike antibodies were present in serum and broncho-alveolar lavages that possessed high virus neutralization capacities to all current SARS-CoV-2 variants of concern. Importantly, the MVA-SARS-2-spike vaccine applied in intramuscular priming and intranasal boosting treatment regimen completely protected hamsters from developing SARS-CoV-2 lung infection and pathology. Together, these results identify intramuscular priming followed by respiratory tract boosting with MVA-SARS-2-S as a promising approach for the induction of local, respiratory as well as systemic immune responses suited to protect from SARS-CoV-2 infections.